Discover new perspectives and gain insights with IDNLearn.com's diverse answers. Join our knowledgeable community to find the answers you need for any topic or issue.
Sagot :
Sure, let's solve the problem step-by-step.
We are given a function [tex]\( f(x) = 3x - 5 \)[/tex] and need to find [tex]\( f(2) \)[/tex].
1. Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 3(2) - 5 \][/tex]
2. Perform the multiplication first:
[tex]\[ 3(2) = 6 \][/tex]
3. Subtract 5 from 6:
[tex]\[ 6 - 5 = 1 \][/tex]
Therefore, [tex]\( f(2) = 1 \)[/tex].
We are given a function [tex]\( f(x) = 3x - 5 \)[/tex] and need to find [tex]\( f(2) \)[/tex].
1. Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 3(2) - 5 \][/tex]
2. Perform the multiplication first:
[tex]\[ 3(2) = 6 \][/tex]
3. Subtract 5 from 6:
[tex]\[ 6 - 5 = 1 \][/tex]
Therefore, [tex]\( f(2) = 1 \)[/tex].
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.